The implication of social media in food introduction and childhood (Research, Society and Development, 2024)
The introduction of food is a physiological milestone in the lives of babies, it influences food choice and the formation of future healthy eating habits, in addition, it suffers various influences from the external environment, such as advertising and media outlets. Therefore, as a result, food insecurities are generated during this early access to social media, resulting in the development of chronic non-communicable diseases and an increase in the consumption of ultra-processed foods. Therefore, the objective of this work was to evaluate the implications of social media in food introduction and in childhood. The work was a literature review, which consulted the Scielo, VHL Portal, Pubmed, EBSCO, LILACS databases, government health websites and Capes Periodical Portal from the last 13 years. When observing that the media influences children's eating habits, using different devices, such as social media to induce the consumption of ultra-processed foods provided. As a result, studies have shown that the dissemination of high-calorie and low-nutrient foods has contributed to an obesogenic environment. Childhood obesity can lead to chronic non-communicable diseases, such as high blood pressure, dyslipidemia, type 2 diabetes mellitus, among others that can appear in childhood, adolescence or even adulthood.